2018
DOI: 10.31893/2318-1265jabb.v6n3p56-61
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characteristics of Indonesian native chickens

Abstract: This research aimed to describe the phenotypic characteristics of local hen varieties. The study sample consisted of twenty 18 week-old hens of the following types: Cemani, black Kedu, white Kedu, and Balinese (Olagan). They were randomly selected from the "Makukuhan" farm in Kedu Temanggung, Central Java Indonesia. The results, which were analyzed using analysis of variance (ANOVA) test, showed significant differences in the quantitative characteristics of body height, body length, and tarsometatarsus length.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
2
11
0
2
Order By: Relevance
“…Regarding APVC, there was no significant variation in phenotypic characteristics of this breed and NMVC, except for body and shank length. The findings in this study are similar to findings by Rofii et al [14] who compared the physical characteristics of different Indonesian native chickens and showed that the body length was significantly different among populations. Subsequently, these two village chicken breeds (NMVC, APVC) can be significantly discriminated from underaged colored broiler chickens based on the two characteristics, including shank length and abdominal fat weight.…”
Section: Carcass Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding APVC, there was no significant variation in phenotypic characteristics of this breed and NMVC, except for body and shank length. The findings in this study are similar to findings by Rofii et al [14] who compared the physical characteristics of different Indonesian native chickens and showed that the body length was significantly different among populations. Subsequently, these two village chicken breeds (NMVC, APVC) can be significantly discriminated from underaged colored broiler chickens based on the two characteristics, including shank length and abdominal fat weight.…”
Section: Carcass Characteristicssupporting
confidence: 91%
“…However, as stated by FAO, the high-efficiency molecular characterization of different animal breeds should be followed by phenotypic characterization [ 13 ]. Phenotypic characterization is the process of identifying distinct breed populations and describing their external and production characteristics in different environments and management systems [ 13 , 14 ]. There are different methods to characterize animals, ranging from linear measurement of morphological traits to the use of molecular techniques [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ciri kualitatif ayam Cemani berbeda dengan ayam Kedu hitam, ayam Kedu putih, dan ayam Bali (Olagan). Ayam Kedu hitam memiliki kesamaan pada warna lidah, jengger, bola mata, dan kaki dengan ayam Kedu putih, namun warna paruh dan warna kulit mirip dengan ayam Bali (Olagan) (Rofii et al 2018). Tingginya keragaman sifat kualitatif ayam lokal hampir muncul pada semua rumpun.…”
Section: Sifat-sifat Kualitatif Dan Kuantitatif Ayam Asli Indonesiaunclassified
“…Therefore, there is need for proper characterisation geared mainly towards improvement in meat and egg production. The first step in such characterisation as outlined by FAO [16] involves the use of phenotypic characteristics which are aspects of physical appearance or other body parameters that can be measured qualitatively and quantitatively [17]. Variations in phenotypes have remained [18], and tolerance or susceptibility of birds to stressful environment could be linked to their phenotypic traits [19,20].…”
Section: Introductionmentioning
confidence: 99%